Stretchable organic printed microlaser. Issue 1 (April 2020) - Yang Zhao, Jin; Chen, Lixuan; Li, Ji; Chen, Hsiao-Hsien; Zhang, Xin; Zhou, Hang
Abstract: Miniaturized lasers with wavelength variability are of crucial importance for various ultracompact photonic devices. Here, we report fine tunable microlasers built by mechanically stretching the flexible microcavities and elastic substrate. The flexible microcavities fabricated by precisely printing dye-doped polymer solution on elastic substrate, enabled whispering-gallery-mode laser under optical pumping. Furthermore, on account of the outstanding structural flexibility of organic materials, reversible wavelength-tunable laser can be realized through adjusting the shape of microcavity via mechanical stretching the elastic substrate. The results will provide guidance for the rational design of photonic devices with novel performances based on the characteristic of organic flexible materials.